Creep behavior of starch-based nanocomposite films with cellulose nanofibrils. (6th March 2015) - Li, Meng; Li, Dong; Wang, Li-jun; Adhikari, Benu
Highlights: Starch–cellulose nanofibrils composites were produced by solution casting method. Presence of CNFs increased the creep resistance of the nanocomposite films. Presence of CNFs increased the storage and loss moduli of nanocomposite films. Abstract: Nanocomposite films were successfully prepared by incorporating cellulose nanofibrils (CNFs) from sugar beet pulp into plasticized starch (PS) at CNFs concentration of 5–20%. The storage ( G ′) and loss ( G ″) moduli, creep and creep-recovery behavior of these films were studied. The creep behavior of these films at long time frame was studied using time-temperature superposition (TTS). The CNFs were uniformly distributed within these films up to 15% of CNFs. The PS-only and the PS/CNFs nanocomposite films exhibited dominant elastic behavior. The incorporation of CNFs increased both the G ′ and G ″. The CNFs improved the creep resistance and reduced the creep recovery rate of the PS/CNFs nanocomposite films. TTS method was successfully used to predict the creep behavior of these films at longer time frame. Power law and Burgers model were capable ( R 2  > 0.98) of fitting experimental G ′ versus angular frequency and creep strain versus time data, respectively.